The Law Enforcement Related to Cyber Crime by Involving the Role of the Cyber Patrol Society in Achieving Justice - Nawawi, Jumriani; Darmawati, Darmawati; Tajuddin, Mulyadi Alrianto; Nutakor , Briggs Samuel Mawunyo (Jurnal IUS Kajian Hukum dan Keadilan, 2023)
This Cyber ​​crime is a crime that is growing massively in Indonesia. In response to this, a cyber police was formed which has the task of maintaining order and obeying the law in society in the digital world. This research aims to initiate a cyber patrol system by prioritizing community participation (cyber patrol society) in realizing justice. This research is normative legal research with a conceptual and statutory approach. The research results confirm that the urgency of reforming the cyber police by involving community participation is intended to minimize abuse of power from the cyber police, especially those that can disturb people's privacy when carrying out activities in cyberspace or the digital world. Efforts to formulate a cyber patrol society in realizing justice for people who are active in the digital world need to be done by involving the community to participate in law enforcement in the digital world. Viewed from the aspect of justice, community participation is needed to ensure that cyber police do not arbitrarily occur when enforcing the law in the digital world. Apart from that, community participation in the cyber patrol system is needed so that there is a preemptive, preventive and educational approach so that public legal awareness when carrying out activities in the digital world can be achieved